Effects of varying retention tree patterns on ground beetle (Coleoptera: Carabidae) taxonomic and functional diversity. Issue 7 (21st July 2021) - Sultaire, Sean M.; Kroll, Andrew J.; Verschuyl, Jake; Landis, Douglas A.; Roloff, Gary J.
Abstract: Managing forests intensively for timber production can homogenize forest structure and, in turn, alter species richness and functional composition of native species communities. Retention forestry, the practice of retaining structural elements during timber harvest, can increase species diversity in recently harvested forests, but its effect on functional trait diversity is less understood. We used a broad‐scale, replicated experiment to evaluate the effect of five tree retention patterns on species and functional trait diversity of ground beetles (Family: Carabidae) within early‐seral production forests in the Pacific Northwest, USA. We found no evidence for differences in carabid species or functional trait richness among treatments when considering species present in retention patches and adjacent clear‐cuts. However, we found evidence for lower taxonomic and functional trait variation between carabid communities present in retention patches and those present in clear‐cut areas of stands when retention was allocated to several small patches. Lower levels of functional trait variation in stands with several small patches were due to specialized predators found less often in small retention patches than in aggregated or riparian retention patches. Our findings indicate that relative to single large or riparian‐associated patches, small retention patches functioned similarly to clear‐cuts within harvested forests and several small patches did not increase species or functional trait richness. At current levels of retention in the region, allocation of trees to a single upland patch or split between riparian and upland patches can increase variation in ground beetle taxonomic and functional composition within harvested forests.